Activation of the p53 pathway induces α-smooth muscle actin expression in both myeloid leukemic cells and normal macrophages. - Secchiero, Paola; Rimondi, Erika; di Iasio, Maria Grazia; Voltan, Rebecca; Gonelli, Arianna; Zauli, Giorgio (J Cell Physiol, 2012)
A range of cell types of mesenchymal origin express α-smooth muscle actin (α-SMA), a protein that plays a key role in controlling cell motility and differentiation along the fibrocyte and myofibroblast lineages. Although α-SMA is often expressed in stromal cells associated to a variety of cancers including hematological malignancies, up to now the role of anti-cancer drugs on α-SMA has not been deeply investigated. In this study, we demonstrated that Nutlin-3, the small molecule inhibitor of the MDM2/p53 interactions, significantly up-regulated the mRNA and protein levels of α-SMA in normal macrophages as well as in p53(wild-type) but not in p53(mutated/null) myeloid leukemic cells. The p53-dependence of α-SMA up-regulation induced by Nutlin-3 was demonstrated in experiments performed with siRNA for p53. Of note, Nutlin-3 mediated up-regulation of α-SMA in OCI leukemic cells was accompanied by cell adhesion to plastic substrate and by reduced cell migratory response in transwell assays. Notably, the role of α-SMA induction in the modulation of myeloid cell migration was clearly documented in α-SMA gene knockdown experiments. In addition, Nutlin-3 significantly up-regulated α-SMA expression in primary endothelial cells, but not in fibroblasts and mesenchymal stem cells (MSC). Conversely, transforming growth factor-β1 up-regulated α-SMA in fibroblasts and MSC, but not in macrophages and endothelial cells. Taken together, these data indicate that Nutlin-3 is a potent inducer of α-SMA in both normal and leukemic myeloid cells as well as in endothelial cells.
Keywords: Actins; Cell Movement; Cells, Cultured; Endothelial Cells; Fibroblasts; Humans; Imidazoles; Leukemia, Myeloid; Macrophages; Mesenchymal Stromal Cells; Piperazines; Proto-Oncogene Proteins c-mdm2; RNA, Small Interfering; Signal Transduction; Transforming Growth Factor beta1; Tumor Suppressor Protein p53